STUDI KERAGAAN AGROEKOSISTEM UNTUK PENGEMBANGAN POTENSI PERTANIAN DI KABUPATEN SUKOHARJO PROPINSI JAWA TENGAH - Jaka Suyana (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2008)
Title : The Study of Habitual Agroecosystem to Develope Agriculture Potential at Sukoharjo Regency in Central Java. The research about habitual agroecosystem to develope agriculture potential at Sukoharjo Regency in Central Java. This research conducted from June until September, 2002. The results showed that Sukoharjo Regency regional base on the Schmidt-Ferguson climate have C-climate type (slightly wet) and D (moderate), can be separate into four (4) agroecosystem, e.i wet land, dry land, mixedfarm, and forest. Wet land agroecosystem grouped into types agroecosystem with parent rock Merapi Volcano, Aluvium, Lawu ejecta, and Wonosari-Punung formation. Dry land agroecosystem grouped into types agroecosystem with parent rock Lawu ejecta, Aluvium, and Mandalika-Wonosari-Punung formation. Mixedfarm agroecosystem grouped into types agroecosystem with parent rock Lawu ejecta, and Mandalika-Wonosari-Punung formation. Whereas forest agroecosystem exist on the Wonosari-Punung formation, and it management strategy toward as community based conservation regional. Keywords : Agroecosystem, Agriculture potential, Sukoharjo Regency